An optimal EoL time point prediction method for mechanical product remanufacturing based on LCA and LCC. (18th May 2020) - Shi, Jun-Li; Ma, Ming-Yang; Wang, Huai-Zhi; Qu, Hong-Wei
ABSTRACT: Remanufacturing is a product recovery strategy resulting in end-of-life (EoL) products being returned to recondition and equivalent to or better than the original. At present, the method of EoL time point determination for product remanufacturing is not available in considering the factors of life cycle energy and cost consumptions. This study proposes an optimal prediction method of EoL time point for product remanufacturing based on life cycle assessment and life cycle cost. First, life cycle assessment and life cycle cost theories are applied to analyze the life cycle energy and cost consumptions. Second, data regression fitting of life cycle energy and cost consumption is applied to obtain the functions of annual energy and cost consumption. Finally, a multi-objective optimization method is used to process the bi-objective functions, and the optimal EoL time point for product remanufacturing is determined. The proposed method is applied to a scroll compressor and obtained an optimal EoL time point for remanufacturing of 7.88 years.